Bacteriological quality evaluation of bedpans in a university hospital - Bros, Aurélie; Deboscker, S; Mielcarek, M; Foeglé, J; Hernandez, C; Ménard, C; Belotti, L; Lavigne, T (International Journal of Infection Control, 2018)
According to the Centers of Disease Control and prevention recommendations, it is necessary to restrain the emergence of multiresistant microorganisms at hospital and control cross-transmission among patients. In this context, one of the main points is the daily strict management of excreta in the care units. We aim to evaluate the safety of reusable bedpans, from a bacteriological point of view, after passing through bedpan washers in our hospital.The present study was conducted from 15 January 2015 to 27 February 2015 in Strasbourg Hospital University. 25 bedpan washers were selected. Three bedpans per bedpan washer were collected for bacterial analysis after cleaning and disinfection. Samples were performed in real conditions, i.e. patients used bedpans without protective bag before passing through bedpan washers.There was no growth (≤1 CFU/25cm2) in 75.3% (55/73) of the samples and 95.8% (70/73) had a result which was below the target value (≤25 CFU/25cm2). Only 3 samples (4.1%), from different bedpan washers, have a result above the target value. A third of the identified bacteria were environmental microorganisms and 2 thirds were skin flora. No indicator microorganism was identified (Staphylococcus aureus, enterobacteria, enterococci, Pseudomonas aeruginosa, Pseudomonas sp, Stenotrophomonas maltophilia, Acinetobacter spp., Candida spp., filamentous fungi).The effectiveness of bedpan washers is quite acceptable regarding the bactericidal activity. Indeed, we expected less good results since a small amount of bedpans are visibly soiled at the end of the cycle. However, it would be of interest to perform a second study evaluating the virucidal and sporicidal activity of the bedpan washers.